(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A low-diversity, relatively well-preserved brachiopod fauna is documented in detail for the first time from the Sandbian–Katian (Upper Ordovician) siliciclastic rocks of the Oxhe Inlier (Belgium), i.e. a small Caledonian inlier included in the Condroz Inlier, whereas some preliminary data are also presented for the Darriwilian–Sandbian (Middle–Upper Ordovician) brachiopods of the central part of the Condroz Inlier (Huy and Vitrival-Bruyère formations), Belgium. The brachiopods from the Oxhe Inlier (Oxhe Formation) were collected from several localities in the Oxhe Inlier where they are associated with trilobites, ostracods, molluscs, echinoderms and machaeridians. The Oxhe Formation yielded one lingulate, one craniate, two strophomenates and three rhynchonellates, while the Huy Formation yielded two lingulates to which are added one strophomenate and two rhynchonellates from the Vitrival-Bruyère Formation (Sart-Bernard Member). These taxa are assigned with variable degrees of confidence to existing taxa or described under open nomenclature. An age range of Darriwilian to Katian is confirmed. Multivariate numerical analyses (Nonmetric Multidimensional Scaling together with Network Analysis) indicate close comparison with other Avalonian faunas. Moreover, the combination of taxa suggests habitats in deeper-water environments around the Avalonian continent.